2020
DOI: 10.1210/clinem/dgaa857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Complications of Pituitary Blastoma

Abstract: Context Pituitary blastoma is a rare, dysontogenetic hypophyseal tumor of infancy first described in 2008, strongly suggestive of DICER1 syndrome. Objective To describe genetic alterations, clinical courses, outcomes, and complications in all known pituitary blastoma cases. Design and Setting: Multi-institutional case series from tertiary pediatric oncology centers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…We subsequently studied DNA from tumor and germline DNA from the parents and two siblings. The patient and siblings inherited a splice-site DICER1 variant from the father; splicing studies revealed that the variant creates an out-of-frame nucleotide sequence predicted to result in a truncated protein, which may be subject to nonsense-mediated decay (30). Despite poor-quality tumor DNA, an RNase IIIb hotspot mutation was weakly, but reproducibly, detected.…”
Section: Recently Investigated Cases Of Pituitary Blastomamentioning
confidence: 99%
See 3 more Smart Citations
“…We subsequently studied DNA from tumor and germline DNA from the parents and two siblings. The patient and siblings inherited a splice-site DICER1 variant from the father; splicing studies revealed that the variant creates an out-of-frame nucleotide sequence predicted to result in a truncated protein, which may be subject to nonsense-mediated decay (30). Despite poor-quality tumor DNA, an RNase IIIb hotspot mutation was weakly, but reproducibly, detected.…”
Section: Recently Investigated Cases Of Pituitary Blastomamentioning
confidence: 99%
“…DICER1 genotyping has been previously reported for 14 cases (3,4,17,18). Sequencing of DICER1 was performed on Case 17 by using the custom-design Access Array (Fluidigm), and an exon trapping assay was used to validate the functional consequence of a newly identified splice-site variant (4, 29,30). In two cases, no molecular information was available, but one of the cases showed strong clinical evidence of DICER1 syndrome (4).…”
Section: Dicer1 Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemically, serum GH and IGF-1 levels were not elevated. Clinically, patients did not present increased growth velocity or tall stature [ 188 ].…”
Section: Somatic Variants In Gh-secreting Pitnetsmentioning
confidence: 99%